Behavior of polyethylene under different triaxial stress states: An experimental and numerical study. (March 2021) - Han, Limei; Zhang, Yi; Xue, Shifeng; Zhou, Bo; Liu, Cuiwei
The behavior of a semi-crystalline polymer under different triaxial stress states is studied through the combination of experimental testing and finite element simulation. Polyethylene round bar specimens with four different notch radii were stretched at crosshead speed of 1 mm/min until fracture. The continuum damage mechanics damage model and Gurson–Tvergaard–Needleman damage model were proposed and applied to the finite element simulation. The results of engineering stress–displacement curves determined from finite element simulation match experimental results. Finite element simulation without considering damage and with the consideration of damage was conducted to determine the damaged and undamaged true stress–strain relationship of polyethylene materials, respectively. Damage evolution model was established based on the degradation of true stress. The finite element model was further applied to study the distribution of stress triaxiality for specimens with different notch radii and the effect of stress triaxiality on damage evolution, critical damage parameters, and fracture strain. The results show that the distribution of the stress triaxiality on the cross section of the specimen is not uniform, and as the stress triaxiality increases, the position where the maximum stress triaxiality occurs moves from the center point to two-third the radius from the center. Furthermore, the damaged true stress and the undamaged true stress increases with the decrease of the stress triaxiality when the strain is below 0.3, but decreases with the increase of stress triaxiality when the strain is larger than 0.3. In addition, it was found that the greater the stress triaxiality, the earlier the onset of damage and the faster the evolution, but the smaller the fracture strain.